A Comparative Study of Lean Startup and Design Thinking to Accelerate Startup Market Adaptation - Diki , Diki Wahyudi (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2025)
This study aims to compare two popular innovation approaches, namely Lean Startup and Design Thinking, in the context of speed of responding to market needs. Lean Startup is known for its focused scientific method that encourages hypothesis testing and product validation through the Build-Measure-Learn cycle, while Design Thinking emphasizes deep understanding of users and the creation of innovative solutions through the process of research, problem definition, ideation, prototyping, and evaluation. Through literature analysis and comparison of the two approaches, this study found that although both have the same goal of creating relevant products, they have different methods and focuses. Lean Startup is more efficient in a dynamic and competitive environment, while Design Thinking produces solutions that are more in line with user needs. This study recommends that companies and innovators consider the specific context of the innovation project being implemented and combine elements of both approaches to achieve optimal results. These findings provide valuable insights into the application of Lean Startup and Design Thinking in product development and innovation.